Adaptive output feedback control of feedforward nonlinear distributed delay systems with unknown delay kernel. Issue 10 (3rd October 2017) - Jia, Xianglei; Chen, Xinkai; Xu, Shengyuan
ABSTRACT: This paper considers the problem of global adaptive output feedback regulation for a class of uncertain feedforward nonlinear distributed delay systems. Compared with the existing results, we reduce the conservatism of the restrictive conditions by combining the dynamic scaling technique and the backstepping method, in particular, uncertain control coefficients and unknown delay kernels are admitted. With the help of the Lyapunov–Krasovskii theorem, a delay-independent output feedback controller is proposed by constructing an input-driven observer with a novel dynamic gain, which guarantees that all the closed-loop signals are globally bounded while rendering the states of original system and the estimate states globally asymptotically to converge to zero as time goes to infinity. Finally, a numerical example is given to illustrate the usefulness of our results.